Streamflow generation across an elevation gradient after the 2020 Cameron Peak Fire - Miller, Quinn, author; Kampf, Stephanie, advisor; Nelson, Peter, committee member; Hammond, John, committee member (Colorado State University. Libraries, 2022)
The western United States is experiencing an increase in catastrophic wildfire in virtually all ecoregions. Many of these fires burn in forested headwaters that communities rely on for water supply, underscoring the need for a greater understanding of how wildfire impacts streamflow timing and magnitude. Though many studies have examined the hydrologic response to fire, the site-specific nature of this type of research has made it difficult to generalize findings. The 2020 Cameron Peak fire burned across a broad swathe of the Colorado Front Range, making it an ideal case study to examine the factors that affect post-fire runoff. The goal of this work is to identify how streamflow responses to rainfall vary from pre-to post-fire conditions and between mountain regions defined by seasonal snow cover and aridity. To this end, we selected three watersheds to compare fire effects on rainfall runoff between snow zones. These watersheds were unburned, moderately burned, and severely burned in each of two snow zones: the high-elevation persistent snow zone, and the mid-elevation intermittent snow zone. These watersheds were instrumented to monitor rainfall and stream discharge throughout water year 2021. To evaluate how wildfire affected runoff, we developed multi-variate statistical models and used Tukey's Honestly Significant Differences test to compare streamflow responses to rainfall between watersheds. Across all burn categories, the high elevation sites were more responsive to rainfall compared to streams at lower elevations; ~50% of rain events produced a streamflow response in the persistent snow zone, compared to ~25% in the intermittent snow zone. In both snow zones, the unburned sites were the least responsive to summer rainfall and had the highest summer baseflows. Although the high elevation streams were more responsive to rain, they did not exhibit evidence of infiltration excess overland flow. Lags between peak rainfall and peak discharge were 1.2-31.3 hr at these sites; in contrast, the low elevation severely burned site had a much more rapid rise to peak discharge (0.6 hr on average) that indicated infiltration excess overland flow. The rainfall intensity threshold necessary for runoff generation at this site was 4 mm hr-1, which agreed with thresholds reported in similar studies of burned areas in this region. We found no evidence that the moderately burned site in the intermittent snow zone generated rapid runoff, likely because that watershed did not experience enough moderate to high burn severity to promote widespread overland flow. Additionally, the flow response at burned sites was uniformly shorter than for the unburned sites in both snow zones. The magnitude of the flow response was higher in the persistent snow zone than in the intermittent snow zone; however, the effect of burn status on streamflow magnitude was difficult to ascertain. These results demonstrate that the streamflow responses to fire vary between snow zones, indicating a need to account for elevation and snow persistence in post-fire risk assessments. Future work in other regions could evaluate whether this snow zone effect is unique to the study area or a common cause of differences in post-fire streamflow.
Keywords: elevation; runoff; streamflow; fire; Cameron Peak; snow zone